Peningkatan hasil belajar mahasiswa melalui metode quantum learning dengan teknik Mind mapping - Andi Mariani Ramlan (Journal of Educational Science and Technology (EST), 2017)
The purpose of this study is to improve the student learning outcomes in the course of Complex Analysis by applying Quantum Learning method with Mind Mapping technique. This research is conducted to give innovation method and technique of lecturer to reach the purpose and result of learning as expected. The research runs from September to December 2013 at the University of Sembilanbelas November Kolaka, Outheast Sulawesi.  The subject of the reserach is the B grade students of class VII 2011 with a total of 34 students. This research is included in Classroom Action Research (CAR). The researchers designed the study in several cycles each cycle with stages: 1) Planning, 2) Implementation; 3) Observation and Evaluation, and 4) Reflection. The students responded is positively to learning by using Quantum Learning method with Mind Mapping technique.  The students' learning achievement is 3,29 from the ideal value of 4,00; and 88,3% Student get A Or B. Then, it is concluded that Quantum Learning method with mind mapping technique can improve student learning outcomes in Complex Analysis program.